2003
DOI: 10.1046/j.1525-1446.2003.20507.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Community‐Health‐Nursing Sensitivity of Six Outcomes for Community Health Nursing with Older Clients

Abstract: A survey research design was used to assess the importance, sensitivity to nursing interventions, and content validity of six client outcomes from the Nursing Outcomes Classification (NOC)). Outcomes relevant for elderly community residents and caregivers were included in a questionnaire mailed to American Nurses Credentialing Center-certified expert community health nurses. Two hundred thirty-nine experts rated specific indicators of the six outcomes for their importance in determining the outcomes and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(25 reference statements)
0
16
0
1
Order By: Relevance
“…This adaptation refers to the validation of NOC indicators, instead of characteristics that define a nursing diagnosis, and the criteria used to include the experts for this validation. The outcome content validation, adapted from the model of diagnosis content validation proposed by Fehring, has been used in various studies (Head et al., ; Head, Maas, & Johnson, ).…”
Section: Methodsmentioning
confidence: 99%
“…This adaptation refers to the validation of NOC indicators, instead of characteristics that define a nursing diagnosis, and the criteria used to include the experts for this validation. The outcome content validation, adapted from the model of diagnosis content validation proposed by Fehring, has been used in various studies (Head et al., ; Head, Maas, & Johnson, ).…”
Section: Methodsmentioning
confidence: 99%
“…Various models are proposed to validate nursing diagnoses; it is highlighted, however, that Fehring's diagnostic content validation model has been widely used in nursing. As nurses are accustomed to this model, it has been used to validate nursing outcomes (12)(13) . The validity of outcome indicators has been estimated based on expert judgments' on their relevance, based on a specific context, given by the ND Self-Care Deficit: bathing/hygiene in adult patients submitted to THR.…”
Section: Methodsmentioning
confidence: 99%
“…The development and validation of community‐level nursing‐sensitive outcomes is consistent with both official specialty organization statements that clarify the focus of PHN as population‐based (American Public Health Association–Public Health Nursing Section, 1996; Quad Council of Public Health Nursing Organizations, 1999) and with population‐based practice focused at individual, family, system, and community levels (Keller, Strohschein, Lia‐Hoagberg, & Schaffer, 1998). Head, Maas, and Johnson (2003) reported that ANCC‐certified community health nursing experts viewed development of community‐level nursing‐sensitive outcomes as essential for PHN practice evaluation and important for the NOC. Although six NOC individual and family caregiver outcomes were judged as having content validity and nursing sensitivity for community practice, experts observed that the contribution of PHN as a specialty could not be adequately described by only individual‐level outcome measures such as self‐care: activities of daily living, caregiver emotional health, health‐promoting behavior.…”
Section: Introductionmentioning
confidence: 99%